Comparative studies on the substrate specificity and defucosylation activity of three α-l-fucosidases using synthetic fucosylated glycopeptides and glycoproteins as substrates. (15th July 2021) - Prabhu, Sunaina Kiran; Li, Chao; Zong, Guanghui; Zhang, Roushu; Wang, Lai-Xi
Graphical abstract: Abstract: Core fucosylation is the attachment of an α-1, 6-fucose moiety to the innermost N -acetyl glucosamine (GlcNAc) in N -glycans in mammalian systems. It plays a pivotal role in modulating the structural and biological functions of glycoproteins including therapeutic antibodies. Yet, few α-l -fucosidases appear to be capable of removing core fucose from intact glycoproteins. This paper describes a comparative study of the substrate specificity and relative activity of the human α-l -fucosidase (FucA1) and two bacterial α-l -fucosidases, the AlfC from Lactobacillus casei and the BfFuc from Bacteroides fragilis . This study was enabled by the synthesis of an array of structurally well-defined core-fucosylated substrates, including core-fucosylated N -glycopeptides and a few antibody glycoforms. It was found that AlfC and BfFuc could not remove core fucose from intact full-length N -glycopeptides or N -glycoproteins but could hydrolyze only the truncated Fucα1, 6GlcNAc-peptide substrates. In contrast, the human α-l -fucosidase (FucA1) showed low activity on truncated Fucα1, 6GlcNAc substrates but was able to remove core fucose from intact and full-length core-fucosylated N -glycopeptides and N -glycoproteins. In addition, it was found that FucA1 was the only α-l -fucosidase that showed low but apparent activity to remove core fucose from intact IgG antibodies. The ability of FucA1 to defucosylate intact monoclonal antibodies reveals an opportunity to evolve the human α-l -fucosidase for direct enzymatic defucosylation of therapeutic antibodies to improve their antibody-dependent cellular cytotoxicity.